Adaptation key terms - Taylor, Anna
The authors highlighted some of the main areas of confusion regarding terminology in the field of community-based adaptation (CBA). They explained how articulating and addressing "frequently asked questions" about CBA can help improve understanding and stimulate discussion. They proposed a broader process of learning and collaborative "sense-making" to help develop a knowledge structure and a shared vocabulary on CBA.